Counterintuitive investment opportunities on the wse. Evidence from the field of asset pricing - Roszkowska, Paulina; Langer, Łukasz K. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
How mispriced is the equity in emerging economies? We join this academic discussion by studying stock returns in today’s Polish stock market. We test for abnormal excess returns using classic and modern asset pricing models. We report the evidence of certain time-varying return patterns that show investment potential. While size, investment, and momentum effects are not unequivocal enough to advertise them as trading opportunities, strategies based on profitability and value anomaly are evident and persistent throughout different investment climates. Counterintuitively, at an aggregated level we report a higher level of mispricing, and thus higher abnormal investment opportunities, in the period of bear market and stable macro-conditions (2000-2006) than during and after the recent global financial crisis (2007-2013). We advocate that in emerging stock markets like the Warsaw Stock Exchange, investors’ asset pricing skills outweigh the effect of international portfolio rebalancing in the process of asset pricing
Argumenta Oeconomica, 2019, Nr 1 (42), s. 21-53
Keywords: asset pricing model; emerging market; abnormal returns; international portfolio diversification